Annular and supra-annular sizing for transcatheter aortic valve implantation (TAVI) in bicuspid aortic valve stenosis (AS): A single centre experience at Sarawak Heart Centre - Khor, How Kiat; Asri, Said; Oon, Yen Yee; SS, Koh; Alan Yean Yip, Fong; Chung, Bui Khiong; Ling, Hwei Sung; Chow, Han Bing; Chan, En Ze; Pang, Ing Xiang; Francis Eng Pbeng, Shu; Leong, Lai Kuan; et al. (Elsevier B.V., 2024)
Transcatheter aortic valve implantation (TAVI) is a proven treatment for severe aortic stenosis (AS) in elderly individuals at high-risk for surgery. Historically, clinical trials have excluded bicuspid AS, hence there is no standardized valve sizing method. Despite increasing TAVI usage in younger patients with bicuspid AS, randomised trials of sizing methods (annular vs. supra-annular: ICD, Wei, and Casper methods) for transcatheter heart valve (THV) remain scarce.